PLANO ESTRATÉGICO DE GESTÃO DE PESSOAS: UM ESTUDO NA VIA PASSOS VEICULOS LTDA - Bergmann, Lia M.; Pizolotto, Maira F.; Vogt, Juliane; Weirich, Lucilete; Zimmermann, Lucia F. (Salão do Conhecimento, 2013)
Resumo